Efficacy of Moringa Leaf Extract Hormesis as Natural Biostimulant on Yield And Bioactive Compounds of Lettuce - Pramanik, S K; Saha, D; Mou, S; Ahammed, S; Siddiquea, T; Bandhan, B S; Roy, L; Hasan, R (Bangladesh Agronomy Journal, 2025)
This study was conducted to assess the effectiveness of moringa (Moringa oleifera Lam.) leaf extract (MLE) as a natural biostimulant on yield and bioactive compounds of lettuce. The trial was conducted during November 2023 to February 2024 with lettuce var. BARI lettuce-1. Twenty plastic pots following complete randomized design with four replications was followed. Four concentrations (3%, 4%, 5% and 6%) of MLE was foliar sprayed into lettuce where a control treatment (tap water) was also considered. Leaf number, leaf length, fresh and dry weight of leaves, SPAD value, total chlorophyll, total phenol, flavonoid and vitamin C were assessed. Correlation and regression analysis among the traits were also carried out. The results show that there was significant improvement in yield traits and bioactive compounds of lettuce except vitamin C due to foliar spray of MLE, where 6% MLE was found to maximize the value of the all studied traits of lettuce. Plants treated with 6% MLE provided maximum improvement by 25.01% in leaf number, 14.11% in leaf length, 20.61% in leaf fresh weight, 36.10% in leaf dry weight, 13.13% in SPAD value, 53.72% in total chlorophyll, 34.17% in total phenol and 19.29% in flavonoid compared to that of control. Correlation analysis among leaf traits and bioactive compounds showed positive connection with each other. Similarly, regression analysis among bioactive compounds exhibited positive correlation regression among the traits. Therefore, MLE could play a significant role as safe and natural biostimulant in improving yield and quality of lettuce through improving the vegetative and bioactive traits of lettuce leaf. Bangladesh Agron. J. 2024, 27(1): 9-18